Soil pH as the chief modifier for regional nitrous oxide emissions: New evidence and implications for global estimates and mitigation. (24th November 2017) - Wang, Yajing; Guo, Jingheng; Vogt, Rolf David; Mulder, Jan; Wang, Jingguo; Zhang, Xiaoshan
Abstract: Nitrous oxide (N2 O) is a greenhouse gas that also plays the primary role in stratospheric ozone depletion. The use of nitrogen fertilizers is known as the major reason for atmospheric N2 O increase. Empirical bottom‐up models therefore estimate agricultural N2 O inventories using N loading as the sole predictor, disregarding the regional heterogeneities in soil inherent response to external N loading. Several environmental factors have been found to influence the response in soil N2 O emission to N fertilization, but their interdependence and relative importance have not been addressed properly. Here, we show that soil pH is the chief factor explaining regional disparities in N2 O emission, using a global meta‐analysis of 1, 104 field measurements. The emission factor (EF) of N2 O increases significantly ( p  < .001) with soil pH decrease. The default EF value of 1.0%, according to IPCC (Intergovernmental Panel on Climate Change) for agricultural soils, occurs at soil pH 6.76. Moreover, changes in EF with N fertilization (i.e. ΔEF) is also negatively correlated ( p  < .001) with soil pH. This indicates that N2 O emission in acidic soils is more sensitive to changing N fertilization than that in alkaline soils. Incorporating our findings into bottom‐up models has significant consequences for regional and global N2 O emission inventories and reconciling them with those from top‐down models. Moreover, our results allow region‐specific development of tailor‐made N2 O mitigation measures in agriculture. Abstract : We identified soil pH as the chief factor modifying regional response in N2 O emission to N fertilization, based on an updated global meta‐analysis of 1, 104 field measurements. Both N2 O emission factor (i.e. EF) and nonlinearity coefficient (i.e. ΔEF) were found to negatively correlated with soil pH. Incorporating our findings into bottom‐up models could help to construct sound global N2 O inventories, to reconcile the discrepancies between top‐down and bottom‐up N2 O estimates, and to develop optimized region‐specific measures for N2 O mitigation from agriculture.